2013
DOI: 10.1007/s00170-013-5226-0
|View full text |Cite
|
Sign up to set email alerts
|

Densification behavior of copper powder during the coupled multi-physics fields-activated microforming

Abstract: External electric field-activated sintering techniques have been widely investigated and applied for the forming of large-sized components. These techniques are, however, rarely utilized for the manufacture of miniature and microsized components. In this paper, a novel, coupled forming, and sintering method is reported, which has been used for the fabrication of microcomponents, wherein the loose powder is loaded directly into the die, followed by simultaneous electrical forming and electric sintering (named c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This period is defined as the main densification realized process where the axial reduction increases rapidly (from -2.9553 mm to -3.3455 mm) with the temperature rising, which is shown in Fig.3. It is worth mentioning that there was a very obvious axial shrinkage of sample that occurred, which is a result of deformation and interface melting of particles and has been noted by authors [5,6,11]. (iv).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…This period is defined as the main densification realized process where the axial reduction increases rapidly (from -2.9553 mm to -3.3455 mm) with the temperature rising, which is shown in Fig.3. It is worth mentioning that there was a very obvious axial shrinkage of sample that occurred, which is a result of deformation and interface melting of particles and has been noted by authors [5,6,11]. (iv).…”
Section: Resultsmentioning
confidence: 65%
“…A novel micro-forming technology, named Micro-FAST (combining micro-forming and FAST), was proposed recently by the present authors for the forming of micro-components. Gears made of 316L stainless and Cu powder at the micro-scale have been fabricated successfully [5,6]. As the process illustrated in Fig.1, Micro-FAST is a method which can be used for the forming of micro-components with a variety of material systems, for instance, metals, ceramics and composites.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the schematic of Micro-FAST. It has been used for the preparation of components with a variety of material systems, such as copper [10], 316 L stainless [11] and WC-Co composites [12]. It has been confirmed that Micro-FAST is a faster and simpler technology to fabricate micro-parts.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, a novel microforming technology, named Micro-FAST (combining microforming and field-activated sintering technology (FAST)), was proposed recently by the present authors for the forming of microcomponents [2][3][4][5]: the process is illustrated in Figure 1. Micro-FAST is a method which can be used for the forming of microcomponents with a variety of material systems, e.g.…”
mentioning
confidence: 99%
“…Moreover, with continuous high pressures being applied and the short forming time, Micro-FAST occurs without coarsening of grains during the densification process [4]. Joule heating is the main heat source during the sintering process, and thus the process has different densification mechanisms compared to those of conventional processes (including FAST or spark plasma sintering (SPS)).…”
mentioning
confidence: 99%